Changing Readers, Changing Texts: Beginning Reading Texts from 1960 to 2010. Issue 3 (October 2015) - Hiebert, Elfrieda H.
Over the past 50 years, substantial changes have occurred in the texts used for the instruction for beginning reading. This article analyzes four prominent perspectives that have most influenced beginning reading instruction texts in the United States over this period. This article examines changes in beginning reading texts in relation to changes in the nation's demographics and young children's literacy-related experiences, including media exposure, availability of children's books, and time spent in nonparental care. These analyses are followed by an examination of the research underlying three assumptions that shape the reading instruction found in all current core reading programs: (a) earlier is better, (b) word repetition is not a factor in learning to read, and (c) one size fits all. The review ends with a call for the careful design and selection of texts for students whose literacy levels are impacted greatly by the quality of their school experiences–-children in high-poverty communities.